The Expression of the Dimensions of Smartness in Cultural Management: The Foundations of the Research - Milkintas, Rytis; Tamošiūnas, Teodoras (Socialiniai tyrimai, 2022)
The aim of the research is to substantiate the methodological foundations of empirical research by revealing the concept of the expression of dimensions of smartness in cultural management. The article formulates theoretical construct based on expression of smartness dimensions in cultural management. This construct is formulating by combining cultural management and smart governance concepts and closely linking cultural management with the implementation of cultural policy and seeing the specifics of smart cultural management. The expression of smartness dimensions at culture management model consist of six main dimensions: strategics, creative development, harmonization of interests in the cultural sector, empowered cultural sector parties, harmony of intellectual and technological capital, the culture of shared value creation. Methodology strategy is based on two philosophical approaches by combining induction and deduction which result is abduction approach. Qualitative analysis was performed of theoretical sources of foreign countries and Lithuania. Another part of qualitative research is based on the interviewing chosen respondents to get information about the expression of smartness dimensions at culture management model functioning. There would be chosen about 30 experts (till data saturation) by using quadruple helix. Experts are chosen from government, science, business and nongovernmental organizations’ sphere. Gained results let to form research results conception which consists of three parts: theoretical model, current situation model, perspective situation model. The trajectory of the change from the current situation model to the perspective situation model helps to highlight the areas requiring improvement of the functioning of the cultural field, planned directions (trends) of change. In future research, it is planned to form the indicators for all 6 theoretical dimensions of the expression of smartness dimensions at culture management model. Analysis based on this theoretical model also will be performed at the state level which provide a comprehensive view of the cultural field current situation and hypothetical perspective situation.